Níveis séricos de enzimas hepáticas em poedeiras comerciais no pré-pico e pico de produção de ovos - Gonçalves, Fernanda Medeiros; Ribeiro, Érico de Mello; Montagner, Paula; Lopes, Mateus Silveira; Anciuti, Marcos Antonio; Gentilini, Fabiane Pereira; Del Pino, Francisco Augusto Bukert; Corrêa, Marcio Nunes (Acta Scientiae Veterinariae, 2018)
Background : : : The biochemistry evaluation of liver enzymes gives evidences about metabolic disorders caused by diseases or nutritional deficiency that influence the hepatic activity. The biochemical profile is usually used as a support for diagnosis of hepatic diseases in pets, however the same evaluation it’s not used in cattle. At the same time, there is a few results and benchmarks for commercial poultry biochemical profile, without a consensus between layer activity, breeder lines, period, age, region, nutrition, and other factors that can interfere in data assurance. AST enzyme is considered a responsive marker in liver disorder in chicken, even if is a nonspecific parameter. GGT can indicate cholestasis and biliary ducts proliferation in chicken liver. The aim is compare the levels of aspartate aminotransferase (AST) e gammaglutamyl transferase (GGT), before and during the pick of egg production. Materials, Methods & Results: Thirty-five Hisex Brown laying hens with 16 weeks of age were used for the research. The birds were distributed in a total of seven birds per cage. The hens received the same feed during the experimental period, varying the nutrition levels according layer stage. The experimental design was in random blocks and the animals were in same environment conditions. The light program used was 16 h of artificial lighting per day, with a dark break of eight hours. Three milliliters per bird were collected before the pick (23 weeks) and during the pick of egg production (31 weeks), always in the morning period with a previous fasting. The blood was collected in left wing vein in vacuum tubes. The biochemistry analyses were made with specifics kits for AST and GGT determination. Two analyses of each parameter were made per blood sample in a total of 70 analyses. Data were submitted to variance analyses and the averages were compared in Tukey in a significance level of 1%. Discussion: The levels of AST and GGT in the pre pick of egg production were significantly higher (P <0,0001) than in the pick of production. During this period (30 to 56 weeks of age) the egg production reaches values upward 90%, corresponding to a stage of higher demand for nutrients, mainly amino acids, to attend maximum potential of hen production. However, feed increase is performed in pre pick of production to stimulate layers to reaches the pick of egg production. Thus, liver are extremely forced to process with efficiency the diets ingredients, causing liver cells lyses putting out their contents, increasing AST and GGT levels. In physiological conditions, both AST and GGT enzymes are found in lower levels in blood and higher concentrations inside liver cells. Therefore, a substantial increase of this liver enzymes are associated with tissue disturbance, increase membrane permeability and liver enzymes escape to blood serum. Based on the available data, it was concluded that increasing feed in the pre pick period causes a higher overload in liver of commercial laying hens, increasing serum levels of AST and GGT enzymes. It is recommended other researches with the main point of set up reference values for layers biochemical profile in different stages of egg production and for different breeders.